Fast Lithium Ionic Conductivity in Complex Hydride‐Sulfide Electrolytes by Double Anions Substitution. Issue 8 (9th July 2021) - Zhang, Tengfei; Shao, Yifei; Zhang, Xiang; Huang, Yuqin; Wang, Shuai; Zhou, Wei; Li, Peng; Xia, Guanglin; Yu, Xuebin
Abstract: Hydride‐based solid‐state electrolytes (SSEs) can maintain their stability against Li metal and exhibit high compatibility with a Li metal anode owing to their reducing property and flexible character. However, poor ionic conductivity at room temperature is a major challenge for hydride materials used as SSEs in a lithium ion battery. In this work, a room‐temperature fast lithium‐ion conductor is explored in response to double anion substitution, (100‐ x )(3LiBH4 ‐LiI)‐ x P2 S5 (LLP x, 0 ≤ x ≤ 50). Among these samples, LLP20 respectively delivers an ionic conductivity up to 3.77 × 10 −4 S cm −1 at 30 °C and 1.0 × 10 −2 S cm −1 at 100 °C, with a stable electrochemical window of 0–5 V. A Li plating/stripping test has been conducted under a current density of 1.0 mA cm −2, which exhibits an excellent stability even after 1000 h. Moreover, the all solid‐state cell exhibits a remarkable electrochemical performance in a wide temperature range including high reversible capacity, good rate capability, and long cycling durability. These outstanding performances present a practical strategy for developing ambient‐temperature, fast ionic conductors for all solid‐state batteries in near future. Abstract : The high temperature phase of LiBH4 with fast ionic conductivity is stabilized by double anions doping at room temperature. Moreover, the all solid‐state batteries exhibit a remarkable electrochemical performance in a wide temperature range from 30 to 100 °C including high reversible capacity, good rate capability, and long cycling durability.